Modernisasi dan Inovasi Pengelolaan Sampah Berbasis Masyarakat di Desa Sumur Gedang Kota Sungai Penuh, Kerinci - Fitri Widiastuti; Riski Hernando; Rafiqi; Hendriyaldi; Dwi Hastuti; Helen Parkhurst (STIKes Ibnu Sina Ajibarang, 2024)
Partners in this PPM activity are Village Apparatus and several community representatives of Sumur Gedang Village, Sungai Full City, Kerinci. Based on the analysis of the situation, the main problem faced by partners today lies in the phenomenon of waste which continues to increase in volume which causes environmental pollution, especially related to cleanliness and health. The increasing population and community activities greatly affect the increasing volume of waste in rural areas. Various kinds of pollution that occur due to piles of garbage so that the impacts caused include environmental damage, changes in health conditions. Support, participation and awareness from various parties, especially waste management drivers, is one of the keys to the success of good waste management. Based on these problems, through this activity, several solutions to solve problems will be provided. The method of implementing activities uses a participatory approach through training and mentoring activities, with measurable achievement targets. The results of PPM activities that have been carried out are obtained as a result of the PPM team has carried out all forms of training and simple practices to partners including in making natural compost by utilizing leftover vegetable pieces from households that can be used as natural fertilizer to fertilize the soil. In addition, the team practiced processing plastic waste to be used as handicrafts and other products which are expected to be attractive and can be resold in the future.